PENGARUH MEDIA FANBASE @KIMJIWOONG_INA TERHADAP PEMENUHAN INFORMASI KOMUNITAS WOONGDEONGIES DI PLATFORM X - Vitaloka Diazony; Ade Budi Santoso (STKIP Subang, 2026)
Fans require information about their idols as a form of fulfilling their information needs. The development of social media has positioned fanbase accounts as one of the key sources for fans to obtain the latest news and activities related to their idols. This study aims to examine the influence of the fanbase media @KIMJIWOONG_INA on the information fulfillment of the Woongdeongies community on the X platform. This research uses a quantitative method with a simple random sampling technique. Data were collected through questionnaires distributed to 100 respondents who are followers of the @KIMJIWOONG_INA account on the X platform. This study applies the Uses and Gratifications Theory, which explains that audiences are active in selecting and using media to fulfill specific needs, one of which is information needs. The results show that the fanbase media @KIMJIWOONG_INA has a positive and significant effect on fans’ information fulfillment. The magnitude of this influence is 49.9%. It can be concluded that the fanbase media @KIMJIWOONG_INA influences the information fulfillment of the Woongdeongies community on the X platform.